Homotopy linear algebra - Gálvez-Carrillo, Imma; Kock, Joachim; Tonks, Andrew (Proceedings of the Royal Society of Edinburgh. Section A. Mathematics, 2018)
By homotopy linear algebra we mean the study of linear functors between slices of the ∞-category of ∞-groupoids, subject to certain finiteness conditions. After some standard definitions and results, we assemble said slices into ∞-categories to model the duality between vector spaces and profinite-dimensional vector spaces, and set up a global notion of homotopy cardinality à la Baez, Hoffnung and Walker compatible with this duality. We needed these results to support our work on incidence algebras and Möbius inversion over ∞-groupoids; we hope that they can also be of independent interest.